2018
DOI: 10.1038/s41419-018-1019-6
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 promotes ERK-mediated mitochondrial Drp1 phosphorylation for chemoresistance through RAGE in colorectal cancer

Abstract: Dysfunctional mitochondria have been shown to enhance cancer cell proliferation, reduce apoptosis, and increase chemoresistance. Chemoresistance develops in nearly all patients with colorectal cancer, leading to a decrease in the therapeutic efficacies of anticancer agents. However, the effect of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission on chemoresistance in colorectal cancer is unclear. Here, we found that the release of high-mobility group box 1 protein (HMGB1) in conditioned medium fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 50 publications
8
117
0
Order By: Relevance
“…Interestingly, nuclear-positive HMGB1 expression had an opposite outcome on survival prognosis, as CRC patients with strongly positive nuclear HMGB1 expression had a better prognosis than other patients. Previous studies involving different cancers concluded that HMGB1 plays a paradoxical role in promoting or suppressing cancer 3 , 5 10 . This is the first time that HMGB1 has been found to play both positive and negative roles in the same study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, nuclear-positive HMGB1 expression had an opposite outcome on survival prognosis, as CRC patients with strongly positive nuclear HMGB1 expression had a better prognosis than other patients. Previous studies involving different cancers concluded that HMGB1 plays a paradoxical role in promoting or suppressing cancer 3 , 5 10 . This is the first time that HMGB1 has been found to play both positive and negative roles in the same study population.…”
Section: Discussionmentioning
confidence: 99%
“…High-mobility group box-1 (HMGB1) protein, also known as amphoterin or HMG1, was discovered in calf thymus and named according to its high electrophoretic mobility in polyacrylamide gels 3 . The biological function of HMGB1 depends on its subcellular localization and expression 4 , whereby HMGB1 can play a paradoxical role in promoting or suppressing cancer during the progression of malignant tumors 3 , 5 10 . Inside the nucleus, HMGB1 is a highly conserved chromosomal protein engaged in DNA repair, transcription and genome stability 3 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Total lysates (30 µg) were separated via 6%-12% SDS-PAGE, transferred onto PVDF membranes (Millipore, MA, USA) [26,27], blocked with 5% nonfat milk, incubated with specific antibodies (in 1% non-fat milk) overnight at 4 • C, and probed with HRP-conjugated secondary antibodies. The blot membrane was then incubated with Immobilon Western Chemiluminescent HRP Substrate (Millipore, MA, USA), analyzed by an ImageQuant™ LAS 4000 biomolecular imager (GE Healthcare, Amersham, UK), processed with Adobe Photoshop, and quantified by using ImageJ software (NIH, MD, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Furthermore, Gly82Ser, which is the single-nucleotide polymorphism (SNP) of RAGE (rs2070600), enhances ligand binding to boost the downstream signaling pathway, which is associated with amplified risk of numerous cancer types; particularly, the frequency of this polymorphism is much higher in late-stage CRC patients (57,58). Thus, polymorphism of RAGE can affect its function.…”
Section: Rage In Cancermentioning
confidence: 99%
“…Moreover, it has been shown that high phospho-Drp1Ser616 in CRC patients is related to a high possibility of developing tumor relapse. Moreover, RAGE-G82S polymorphism (rs2070600) has high ligand affinity and is related to high phospho-Drp1Ser616 in tumor microenvironment (57) (Figure 4).…”
Section: Hmgb1mentioning
confidence: 99%